Measuring the Outcomes of Maternal COVID-19-related Prenatal Exposure (MOM-COPE): study protocol for a multicentric longitudinal project. Issue 12 (31st December 2020) - Provenzi, Livio; Grumi, Serena; Giorda, Roberto; Biasucci, Giacomo; Bonini, Renza; Cavallini, Anna; Decembrino, Lidia; Drera, Bruno; Falcone, Rossana; Fazzi, Elisa; Gardella, Barbara; Giacchero, Roberta; et al.
Abstract : Introduction: COVID-19 is a highly infectious respiratory disease that rapidly emerged as an unprecedented epidemic in Europe, with a primary hotspot in Northern Italy during the first months of 2020. Its high infection rate and rapid spread contribute to set the risk for relevant psychological stress in citizens. In this context, mother–infant health is at risk not only because of potential direct exposure to the virus but also due to high levels of stress experienced by mothers from conception to delivery. Prenatal stress exposure associates with less-than-optimal child developmental outcomes, and specific epigenetic mechanisms (eg, DNA methylation) may play a critical role in mediating this programming association. Methods and analysis: We present the methodological protocol for a longitudinal, multicentric study on the behavioural and epigenetic effects of COVID-19-related prenatal stress in a cohort of mother–infant dyads in Northern Italy. The dyads will be enrolled at 10 facilities in Northern Italy. Saliva samples will be collected at birth to assess the methylation status of specific genes linked with stress regulation in mothers and newborns. Mothers will provide retrospective data on COVID-19-related stress during pregnancy. At 3, 6 and 12 months, mothers will provide data on child behavioural and socioemotional outcomes, their own psychological status (stress, depressive and anxious symptoms) and coping strategies. At 12 months, infants and mothers will be videotaped during semistructured interaction to assess maternal sensitivity and infant's relational functioning. Ethics and dissemination: This study was approved by the Ethics Committee (Pavia). Results will be published in peer-reviewed journals and presented at national and international scientific conferences. Trial registration number: NCT04540029 ; Pre-results.